School directors training needs and educational inspection: guidelines for action towards educational improvement and inclusion - Tejeiro Gallego, Federico (Avances en Supervisión Educativa, 2023)
Educational research indicates that an improving school has effective governance, with distributed leadership that fosters educational inclusion. In this sense, we consider that the Educational Inspection has an essential role in a good development of the professional competencies of the managerial function and, therefore, in the achievement of an inclusive school. On the other hand, we believe that to propose appropriate actions, we must be aware of training needs of directors. This article collects the results of the research carried out, through surveys with open questions, to 76 directors of Infant and Primary schools in the province of Seville, to find out what training they have and what they demand, what vision they have of the inclusive school and how they develop it together with distributed leadership. The conclusions offer action guidelines for inspectors to be able to advise schools on their way to educational improvement.
Keywords: training; school principals; educational advice; inclusion; leadership; educative inspectorate